Nazwy dawnego drewnianego przyrządu do zdejmowania butów z cholewami 30 lat po Atlasie języka i kultury ludowej Wielkopolski (na przykładach z wybranych wsi wielkopolskich) - Kobus, Justyna (Slavia Occidentalis, 2015)
The article describes the names of the old wooden instrument to remove the top boots from Greater Poland. the author confronted contemporary materials with the old material, especially as described in the Atlas of language and folk culture of Greater Poland and other available publications. Article is part of a series of studies entitled 30 years after Atlas language and folk culture of Greater Poland, which is realized in the Section of Dialectological AMU.